Biochar Amendments Facilitate Methane Production by Regulating the Abundances of Methanogens and Methanotrophs in Flooded Paddy Soil - Gao, Jiakai; Liu, Ling; Shi, Zhaoyong; Lv, Jialong (Frontiers in Soil Science, 2022)
The application of biochar in conjunction with fertilizer in agricultural production is one of the most promising types of management to improve soil quality. However, the effects on the soil microbial community and methane (CH4) emissions from the interactive mechanisms of biochar combined with fertilizer are unclear. In this study, soil column trial was conducted to monitor the surface water nitrogen, dissolved organic carbon (DOC) and CH4 emission dynamics during the process of leaching. Additionally, bacterial and archaeal communities of the soil (0-10 cm) amended with biochar derived from different pyrolysis temperatures (300°C, 500°C, and 700°C) were also analyzed. High-throughput sequencing revealed that the soil archaeal and bacterial community diversities increased under the biochar amendments. The CH4 emission flux of all the treatments in the whole leaching period ranged from 0.0001 to 2.04 μg m-2 h-1, and the DOC ranged from 1.86 to 24.4 mg L-1. Our results showed that biochar amendments significantly increase the soil pH, total nitrogen (TN), and DOC contents, while inhibiting the loss of NO3--N during leaching. In addition, biochar addition increased the paddy soil CH4 emissions, which ascribed to the increasing ratio of the abundances of methanogens to methanotrophs. Consequently, the higher CH4 emissions were probably caused by the stimulation of methanogenic archaea under the biochar amendments. Thus, the results obtained in this study can be applied to guide the application of biochar on greenhouse gas emissions in paddy soil.